Offerings to the discerning eye : an Egyptological medley in honor of Jack A. Josephson - D'Auria, Sue.; Josephson, Jack A. (Culture and History of the Ancient Near East, 2010)
Egyptologist Jack A. Josephson, a writer and researcher in the tradition of the "gentleman scholar," has achieved broad recognition as an authority in Egyptian art history. His lucid investigative analyses have probed and redefined the limits of inquiry, expanded research parameters, and broadened perspectives, emphasizing the undeniable contributions of art history in an intra-disciplinary framework. This volume of collected essays is dedicated to Josephson by distinguished friends and colleagues, a select roster including eminent, established scholars in the field of Egyptology and rising stars of the younger generation. Josephson views Egyptian art history as a critical but neglected area of study, and is a strong proponent of its reinstatement in the academic curriculum as an essential component in the formation of new cadres. The quality of the articles in this Egyptological medley is a tribute to the honoree and an affirmation of the esteem of his peers, while the range of subjects and variety of themes addressed reflect the degree to which he has, in his own scholarship, undertaken to implement his ideal.